Denison, Jackson County - Eaves, Tyler (Kansas State University, The Chapman Center for Rural Studies, 2016)
This is a history of Denison, Kansas. Located in Garfield and Cedar Townships in Jackson County, between the dates of 1887 and 2016, this story is a topical examination of the churches through the use of photographs, newspapers, and historical accounts.
Tyler Eaves, “Denison, Jackson County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/173.
Keywords: A.D Walker; Cedar Township; Denison Methodist Church; Denison Presbyterian Church; Jackson County; Northwestern Railroad